The relationship among oil, natural gas and coal consumption and economic growth in BRICTS (Brazil, Russian, India, China, Turkey and South Africa) countries - Bildirici, Melike E.; Bakirtas, Tahsin (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The causality relationship between economic growth and coal, natural gas and oil consumption was investigated using the ARDL (autoregressive distributed lag bounds) testing approach for the 1980-2011 period in Brazil, Russian, India, China, Turkey and South Africa. According to long-run and strong causality results, there is bi-directional causality between oil energy consumption and Y for all countries. The long-run causality and strong causality results between coal consumption and economic growth indicated that there is bi-directional causality for China and India. According to long-run causality results and a strong causality result, there are bi-directional causality relationships between NGC (natural gas energy consumption) and Y for Brazil, Russia and Turkey. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Oil consumption; Coal consumption; Natural gas consumption; ARDL (autoregressive distributed lag bounds); Granger causality; DISAGGREGATE ENERGY-CONSUMPTION; ELECTRICITY CONSUMPTION; CAUSAL RELATIONSHIP; INDUSTRIAL-PRODUCTION; COINTEGRATION ANALYSIS; STRUCTURAL BREAKS; ERROR-CORRECTION; CO2 EMISSION; REAL INCOME; Thermodynamics; Energy & Fuels